Hermeneutika Hadis Sebagai Solusi Penyelesaian Hadis Mukhtalif tentang Larangan Wanita Ziarah Kubur: 1. Introduction, 2. Literature Review, 3. Research Methods, 4. Results and Discussion of the Application of Hadith Hermeneutics to the Mukhtalif Hadith concerning Grave Pilgrimages for Women, 5. Conclusions and Suggestions - Sabila, Ahmad Ahda; Saputra, Gusti Rian (Maqasid: Jurnal Studi Hukum Islam, 2024)
Abstract: Textual interpretation of hadith still dominates. As time progresses, interpretation uses patterns of contextualization of hadith as a response to the lack of hadith texts and limited textual meaning of hadith. So it is considered no longer relevant to the times. According to commentators, contextualization of hadith using a hermeneutical approach can be an alternative to enrich the interpretation of hadith, especially the mukhtalif hadith regarding the prohibition of women visiting graves. This research uses library research methods, with primary data sources from books and journals on the topic of hermeneutics. Meanwhile, secondary data comes from books and journals with the theme of the hadith prohibiting women from visiting graves. The data was analyzed using descriptive analytical methods to find the concept of hermeneutics in understanding the hadith which were considered contradictory. The research results show that the core message (significance/magzā) underlying the basic hadith text is that it is sunnah to visit graves for men or women because it reminds them of death and can always be developed in practice so that it can give rise to other problems for human life. Meanwhile, the core message (significance/magzā) that is not true, such as the prohibition on grave pilgrimages for both men and women because it causes mafsadah/'illat law (forgetting obligations as a husband/father, or as a wife/mother) when done frequently, should be done as much as possible. not practiced in order to prevent humans from things that can cause mafsadah and imbalance in their lives. Keywords: Hermeneutic, Mukhtalif Hadith, and Women Pilgrimage to the Grave.